On Examining Specificity in Latent Construct Indicators. Issue 6 (1st November 2016) - Raykov, Tenko; Marcoulides, George A.
Abstract : A latent variable modeling procedure for examining specificity in any indicator of a common factor for a set of repeatedly administered measures is outlined in a longitudinal design setting with measurement invariance and specificity stability over time. The method permits one to test whether there is specificity in a given indicator and in the affirmative case allows one to point and interval estimate the specificity variance in that measure. The discussed procedure is readily applicable with popular software, is based on empirically testable conditions, and is illustrated with an example.